Acoustical diagnostics of cracks in beam like structures - MAJKUT, L. (Archives of Acoustics, 2006)
In this paper, the acoustical symptoms of a constructional element with an edge non-propagating crack on the example of a cantilever beam are searched. In this work the influence of a crack on flexural natural frequency was analysed. The crack is substituted by a rotational spring, which flexibility is calculated using the Castigliano theorem and the laws of the fracture mechanics.In this work the changes in the first and second natural frequency of the flexural vibrations are showed as a function of location and depth of the crack. The acoustic signal measured with a microphone placed above the beam is used for diagnostic systems.Changes in the natural frequency cannot be used for the identification of a small crack (the depth is less than 10% of beam height). For the detecting of a smaller crack, the effect of coupled different modes of vibration is presented. The paper presents a modelling and analysis algorithm for cracked Euler-Bernoulli beams by considering the coupling between the bending and axial vibration modes. The analysis of the coupled vibrations showed that additional resonance frequencies appeared in the acoustic spectrum.